Weak electron–phonon coupling and enhanced thermoelectric performance in n-type PbTe–Cu₂Se via dynamic phase conversion - Wu, Ming (2023)
This study investigates Ga-doped n-type PbTe thermoelectric materials and the dynamic phase conversion process of the second phases via Cu2Se alloying. Introducing Cu2Se enhances its electrical transport properties while reducing its lattice thermal conductivity (κlat) via weak electron–phonon coupling. Cu2Te and CuGa(Te/Se)2 (tetragonal phase) nanocrystals precipitate during the alloying process, resulting in Te vacancies and interstitial Cu in the PbTe matrix. At room temperature, Te vacancies and interstitial Cu atoms serve as n-type dopants, increasing the carrier concentration and electrical conductivity from ≈1.18 × 1019 cm−3 and ≈1870 S cm−1 to ≈2.26 × 1019 cm−3 and ≈3029 S cm−1, respectively. With increasing temperature, the sample exhibits a dynamic change in Cu2Te content and the generation of a new phase of CuGa(Te/Se)2 (cubic phase), strengthening the phonon scattering and obtaining an ultralow κlat. Pb0.975Ga0.025Te-3%CuSe exhibits a maximum figure of merit of ≈1.63 at 823 K, making it promising for intermediate-temperature device applications.